Extending residential care through telephone counseling: Initial results from the Betty Ford Center Focused Continuing Care protocol - Cacciola, John S. (2008)
There is increasing evidence that a chronic care model may be effective when treating substance use disorders. In 1996, the Betty Ford Center (BFC) began implementing a telephone-based continuing care intervention now called Focused Continuing Care (FCC) to assist and support patients in their transition from residential treatment to longer-term recovery in the “real world”. This article reports on patient utilization and outcomes of FCC. FCC staff placed clinically directed telephone calls to patients (N=4094) throughout the first year after discharge. During each call, a short survey was administered to gauge patient recovery and guide the session. Patients completed an average of 5.5 (40%) of 14 scheduled calls, 58% completed 5 or more calls, and 85% were participating in FCC two months post-discharge or later. There was preliminary evidence that greater participation in FCC yielded more positive outcomes and that early post-discharge behaviors predict subsequent outcomes. FCC appears to be a feasible therapeutic option. Efforts to revise FCC to enhance its clinical and administrative value are described.